2021
DOI: 10.1186/s12889-021-11679-8
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of social stigma among patients tested positive for COVID-19 and their family members: a qualitative study

Abstract: Background Social stigma against persons infected with COVID-19 is not uncommon. This qualitative study aimed to explore the experience of social stigma among COVID-19 positive patients and their family members. Method This cross-sectional study was conducted between April to June 2020 in Malaysia. Patients who have recovered from COVID-19 for at least 1 month and their family members who were tested with negative results, Malaysian and aged 18–65 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 34 publications
3
54
0
Order By: Relevance
“…Likewise, in two studies from Ghana, patients with COVID-19 reported experiencing stigma and discrimination ( 14 , 15 ). In the study from Malaysia, COVID-19-recovered participants expressed experiencing being labeled and blamed by the people around them ( 16 ). While being novel among the older population, our study extends and supplements previous research among younger adults ( 8 , 11 13 ) to enrich our understanding of COVID-19 stigma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, in two studies from Ghana, patients with COVID-19 reported experiencing stigma and discrimination ( 14 , 15 ). In the study from Malaysia, COVID-19-recovered participants expressed experiencing being labeled and blamed by the people around them ( 16 ). While being novel among the older population, our study extends and supplements previous research among younger adults ( 8 , 11 13 ) to enrich our understanding of COVID-19 stigma.…”
Section: Discussionmentioning
confidence: 99%
“…In another study from Ghana, nearly half of the participants exhibited stigma and discriminatory tendencies toward COVID-19 survivors ( 15 ). In the study from Malaysia, COVID-19-recovered participants expressed experiencing being labeled and blamed by the people around them ( 16 ). For several reasons, mentioned in the following paragraph, we believe that the level of COVID-19 stigma would be higher among older adults, in general, and more especially among Bangladeshi older adults, which warrants a separate study.…”
Section: Introductionmentioning
confidence: 99%
“…In this group the perceived susceptibility to the virus may have been low [ 37 ] and resulted in less interest in this topic. Persons who believed to have already had COVID-19 tended not to use personal networks, which might indicate stigmatization of persons with COVID-19 at the early stage of the pandemic [ 38 ]. However, among this group, those with high health literacy used personal networks more often than those with low health literacy, indicating that people with a high health literacy might be more capable to communicate about their disease experience with others.…”
Section: Discussionmentioning
confidence: 99%
“…However, the nature of the threat that imposed social and physical distancing eroded to a great extent the social cohesion and support that Gazans usually rely on during crisis. Stigma and social isolation, primarily experienced by the COVID-19 survivors and their families, suggests a negative impact on the physical, mental, and emotional wellbeing amongst this group (32,33) and could worsen the psychological wellbeing especially for those who had already mental health di culties prior to the pandemic. A recent study in occupied Palestine found that, in a social distancing era, close social support becomes vital for mental health and exerts a stronger contribution to positive wellbeing than the general sense of belonging to a community and trust in government (34).…”
Section: Discussionmentioning
confidence: 99%